The impact of office chair features on lumbar lordosis, intervertebral joint and sacral tilt angles: a radiographic assessment. Issue 10 (3rd October 2017) - De Carvalho, Diana; Grondin, Diane; Callaghan, Jack
Abstract: Background: The purpose of this study was to determine which office chair feature is better at improving spine posture in sitting. Method: Participants ( n = 28) were radiographed in standing, maximum flexion and seated in four chair conditions: control, lumbar support, seat pan tilt and backrest with scapular relief. Measures of lumbar lordosis, intervertebral joint angles and sacral tilt were compared between conditions and sex. Results: Sitting consisted of approximately 70% of maximum range of spine flexion. No differences in lumbar flexion were found between the chair features or control. Significantly more anterior pelvic rotation was found with the lumbar support ( p = 0.0028) and seat pan tilt ( p < 0.0001). Males had significantly more anterior pelvic rotation and extended intervertebral joint angles through L1–L3 in all conditions ( p < 0.0001). Conclusion: No one feature was statistically superior with respect to minimising spine flexion, however, seat pan tilt resulted in significantly improved pelvic posture. Practitioner Summary: Seat pan tilt, and to some extent lumbar supports, appear to improve seated postures. However, sitting, regardless of chair features used, still involves near end range flexion of the spine. This will increase stresses to the spine and could be a potential injury generator during prolonged seated exposures.